Toward brain-computer interfacing - Dornhege, Guido (MIT Press, 2007)
This volume presents a timely overview of the latest BCI research, with contributions from many of the important research groups in the field.
"A Bradford book."
Keywords: Brain-computer interfaces.; elektronické knihy; electronic books